Cognitive Behavior Therapy Compare To Campaign Advertisement Programs In Reducing Aggressive Driving Behavior - Santoso, Guritnaningsih A.; Maulina, Dewi; Indirasari, Dyah T.; Saraswati, Ina (UI Scholars Hub, 2011)
This study was conducted to examine the effectiveness of three intervention programs, i.e. CBT (Cognitive Behavior Therapy), humor appeal advertisements (positive ads), and fear appeal advertisements (negative ads) in reducing aggressive driving behavior. 196 young adults age between 18–35 years old, who are considered to be at risk in performing aggressive driving behavior had completed four self report inventories. The four inventories measures perception on traffic conditions, degree of frustration, anger emotion, and driving behavior. Analysis of mix factorial desigm shows that CBT intervention program is more effective than the advertising intervention program, particularly in reducing the degree of frustration and emotional upset. However, no significant difference between humor appeal and fear appeal advertisements in reducing the level of frustration and anger emotion. Moreover, CBT program as well as the other two advertising intervention programs is not sufficient enough to reduce driving behavior. Based on the A-BC Theory of Emotonal Arousal proposed by Ellis, this result indicates that safety driving behavior (factor C) among young drivers cannot be achieved through these intervention programs, although their belief and emotion (factor B) has been changed. This study implies that other modification behavior technique, i.e. strong penalty from the author (police) is needed to encourage safer driving behavior of Indonesian young driver